CREATION OF DARIA VIKONSKA IN LITERATURE-CRITICAL RECEPTION OF PERIODICALS OF 30-H YEARS OF ХХ-th AGE - Tabachin, L. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
On material of epistolary and literature critical publications of 30th years ХХ of age aesthetically ideological-beautiful bases, study strategies of literature and evolutional stages of creation of Daria Vikonska are reflected, the picture is widespread of specific of west Ukrainian literary process of the noted period.